Data-based Inverse Kinematic Control for Multi-section Soft Manipulator - Matos, Victor Santos; Novaes, Luis Victor C.; Mendes, João Vitor S.; Silva, Lucas Cruz Da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Soft manipulators present safe interaction with facilities and forms of life, and inherent dexterity, that demands a complex control system to precisely operate its theoretically infinite degrees of freedom. This article presents a form of data-based inverse kinematic (IK) control for a soft tendon-driven manipulator, with a closed-loop form to help the disturbance reduction to deal with multiple actuated sections, where the position of the end-effector and the middle-section can be explicitly defined. The IK is mapped by a neural network based on simulation training data from the SOFA framework simulator, with the evaluation for the best structure. Tests were conducted in the simulated manipulator, indicating a satisfactory control performance, even in an unstructured environment.